Sustained ocean cooling insufficient to reverse sea level rise from Antarctica - Alevropoulos-Borrill, Alanna; Golledge, Nicholas R.; Cornford, Stephen L.; Lowry, Daniel P.; Krapp, Mario (Communications earth & environment, 2024)
Global mean sea level has risen at an accelerating rate in the last decade and will continue to rise for centuries. The Amundsen Sea Embayment in West Antarctica is a critical region for present and future ice loss, however most studies consider only a worst-case future for the region. Here we use ice sheet model sensitivity experiments to investigate the centennial scale implications of short-term periods of enhanced ocean driven sub-ice shelf melting on ice loss and assess what future reduction in melting is necessary to mitigate ice stream retreat and offset global sea level rise. Our findings reveal that restoring elevated melt rates to present-day levels within 100 years causes rates of ice discharge to immediately decline, thereby limiting the overall sea level contribution from the region. However, while ice stream re-advance and slowed ice discharge is possible with reduced basal melting, a centennial scale increase in accumulation must occur to offset the extensive ice loss.